2021
DOI: 10.1016/j.lanepe.2021.100093
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ symptoms of anxiety and depression before and during the Covid-19 outbreak – A prospective population-based study of teenagers in Norway

Abstract: Background Lockdown policies related to the Sars-Cov-2 pandemic has potential negative consequences for mental health in youths. Methods Anxiety and depressive symptoms were assessed in 3 572 adolescents, age 13 to 16 using the Hopkins Symptom Checklist (HSCL-10), in a representative longitudinal survey of Norwegian youths between February 2019 (T1) and June 2020 (T2). Predictors for symptom change were analysed with linear mixed-effects models. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
137
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 40 publications
16
137
0
3
Order By: Relevance
“…However, the increase of about 2.13 units on a scale from 0 to 100 shows that the effect is of a moderate magnitude and seems to be considerably smaller than what has been found in studies on adults. The rather moderate increases are in accordance with ndings from longitudinal studies on adolescents from the beginning of the pandemic that observed rather small changes in mental health problems 3,6 . Interestingly, contrary to expectations, we found no adverse effect of the pandemic on adolescents' loneliness.…”
Section: The Effect Of the Covid-19 Pandemic On Adolescentssupporting
confidence: 89%
See 2 more Smart Citations
“…However, the increase of about 2.13 units on a scale from 0 to 100 shows that the effect is of a moderate magnitude and seems to be considerably smaller than what has been found in studies on adults. The rather moderate increases are in accordance with ndings from longitudinal studies on adolescents from the beginning of the pandemic that observed rather small changes in mental health problems 3,6 . Interestingly, contrary to expectations, we found no adverse effect of the pandemic on adolescents' loneliness.…”
Section: The Effect Of the Covid-19 Pandemic On Adolescentssupporting
confidence: 89%
“…However, these longitudinal studies do not disentangle effects of the pandemic from normative aging processes in adolescence. To illustrate, a Norwegian longitudinal study indicated that increases in depression and anxiety during the pandemic were caused by adolescents getting older, rather than by effects of the pandemic 6 . Large-scale repeated cross-sectional studies are therefore important to provide more information about the effect of the pandemic on adolescent mental health.…”
Section: Previous Research On the Impact Of The Pandemic On Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the effect of the pandemic on mental health and substance use is likely to be more pronounced among other subgroups, such as youth living in poverty or with preexisting mental health conditions. With research rapidly emerging on these important issues, 2,3,6,29 more targeted interventions can be developed to mitigate the negative impact of the pandemic on adolescent mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic and the restrictions implemented to prevent and contain its transmission have caused widespread disruptions in the lives of adolescents and their families. 1 Initial findings on adolescent mental health during COVID-19 indicate cause for concern, with study findings suggesting an increase in depressive symptoms [2][3][4][5][6] (particularly in adolescent girls 2,[7][8][9] ) and alcohol consumption. 10 However, the rapidly accumulating evidence on the effect of COVID-19 on adolescent mental health has been limited by use of convenience samples and inadequate baseline measures to accurately capture the pandemic's unfolding impact.…”
Section: Introductionmentioning
confidence: 99%